Properties of solutions of the cauchy problem for essentially infinite-dimensional evolution equations - Mal'tsev, A. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We investigate properties of solutions of the Cauchy problem for evolution equations with essentially infinite-dimensional elliptic operators.